Application of ionic liquid with pineapple leaf juice in microbial growth inhibition - Norazwina, Zainol; Loh, Jenny; Rozaimi, Abu Samah (2021)
Pineapple plants have been affected badly by microbe-causing diseases in Malaysia. Several chemical and natural microbe growth inhibitor (MGI) agents are believed that they are able to stop the diseases. Ionic Liquid (IL) posses high antimicrobial potential due to its large organic cations such as ammonium, imidazolium and etc while extracted pineapple leaf juice (PLJ) are believed to contain these MGI properties due to its natural phenolic compound which acts as a defensive mechanism. Therefore, ionic liquid pineapple leaf juice (ILPLJ) is seen as potential valuable product in controlling diseases on pineapple plants. From this research, the best microbial growth inhibition time is 31.25 min.